PENINGKATAN HASIL BELAJAR IPS MELALUI MODEL PEMBELAJARAN KOOPERATIF TIPE TALKING STICK PADA MURID KELAS V SD INPRES PUNRANGA KECAMATAN PUJANANTING KABUPATEN BARRU - Abrina Maulidnawati Jumrah (AIJER: Algazali International Journal Of Educational Research, 2018)
Abstract: Improving Social Studies Learning Outcomes Through Cooperative Learning Model Talking Stick Type in Grade V Students of SD Inpres Punranga, Pujananting District, Barru Regency. The purpose of this study was to improve social studies learning outcomes through the application of the Talking Stick Type Cooperative Learning Model to fifth grade students of SD Inpres Punranga, Pujananting District, Barru Regency. The approach used in this study is a Qualitative approach with this type of research is Classroom Action Research (CAR) in its implementation consists of 2 (two) cycles, where each cycle consists of 2 meetings. The focus of the fifth grade teacher and student research was in SD Inpres Punrangan, Pujananting District, Barru Regency. Data collection techniques in research are observation, testing and documentation. The subject of this study The subjects of this study were fifth grade students of SD Inpres Punranga, Pujananting District, Barru District, with 21 students consisting of 12 men and 10 women. The results showed that the implementation of cooperative learning type talking stick was able to improve social studies learning outcomes. This is indicated by an increase in student learning activities and outcomes. The increase can be seen in the comparison of the first cycle the number of students who complete the complete percentage is 42.86% which is categorized as being. In the second cycle there was an increase, namely the percentage of 85.74% so that it had reached complete completeness classically.